Modeling and Analysis of A Prey-Predator System Incorporating Fear, Predator-Dependent Refuge, with Cannibalism In Prey - Abdul ghafour, Ahmed Sami; Naji, Raid Kamel (Iraqi Journal of Science, 2024)
The relationship between prey and predator populations is hypothesized and examined using a mathematical model. Predation fear, cannibalism among the prey population, and a refuge reliant on predators are predicted to occur. This study set out to look at the long-term behavior of the proposed model and the effects of its key elements. The solution properties of the model were investigated. All potential equilibrium points' existence and stability were looked at. The system's persistence requirements were established. What circumstances could lead to local bifurcation near equilibrium points was uncovered. Suitable Lyapunov functions are used to study the system's overall dynamics. Numerical simulations were conducted to verify the model's derived long-term behavior and understand the implications of the model's primary parameters in order to support the analytical conclusions. It is observed that the system undergoes different types of local bifurcation including Hopf bifurcation.